Fast-solving thermally thick model of biomass particles embedded in a CFD code for the simulation of fixed-bed burners. (15th November 2015) - Gómez, M.A.; Porteiro, J.; Patiño, D.; Míguez, J.L.
Highlights: A thermally thick treatment is used to simulate of fuel the thermal conversion of solid biomass. A dynamic subgrid scale is used to model the advance of reactive fronts inside the particle. Efficient solution algorithms are applied to calculate the temperatures and volume of the internal layers. Several tests were simulated and compared with experimental data. Abstract: The thermally thick treatment of fuel particles during the thermal conversion of solid biomass is required to consider the internal gradients of temperature and composition and the overlapping of the existing biomass combustion stages. Due to the implied mixture of scales, the balance between model resolution and computational efficiency is an important limitation in the simulation of beds with large numbers of particles. In this study, a subgrid-scale model is applied to consider the intraparticle gradients, the interactions with other particles and the gas phase using a Euler–Euler CFD framework. Numerical heat transfer and mass conservation equations are formulated on a subparticle scale to obtain a system of linear equations that can be used to resolve the temperature and position of the reacting front inside the characteristic particle of each cell. To simulate the entire system, this modelling is combined with other submodels of the gas phase, the bed reaction and the interactions. The performance of the new model is tested using published experimental results for the particle and the bed. Similar temperatures are obtained in the particle-alone tests. Although the mass consumption rates tend to be underpredicted during the drying stage, they are subsequently compensated. In addition, an experimental batch-loaded pellet burner was simulated and tested with different air mass fluxes, in which the experimental ignition rates and temperatures are employed to compare the thermally thick model with the thermally thin model that was previously developed by the authors. The results show a better approximation of the model in this study, which addresses some of the main limitations of a thermally thin model regarding the bed reaction stability in overstoichiometric regimes.